2015
DOI: 10.14444/2052
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Derived Morphogenetic Protein-2 Induces Cell Migration and Its Chondrogenic Potential in C28/I2 Cells

Abstract: The study shows that C28/I2 cells can migrate under the influence of CDMP-2 as a chemoattractant or migration stimulator, suggestive of an effect on chondrocytic cells in the intervertebral disc. Further, CDMP-2 can stimulate C28/I2 cells to proliferate and synthesize key extracellular matrix proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Interestingly, at high concentrations (800 ng/mL) GDF6 was also shown to act as a potent chemoattractant for NP cells with similar responses observed to potent chemoattractants, such as fetal calf serum (FCS) . This result supports evidence that GDF6 can also act as a chemoattractant to chondrocytes . In a recent RNA sequencing study investigating regulatory networks controlling ECM synthesis in the human, IVD, GDF6, and GDF5 were identified as important human NP (but not AF) coregulatory gene networks .…”
Section: The Effect Of Supplementation With Gdfs On Disc Cells and Chmentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, at high concentrations (800 ng/mL) GDF6 was also shown to act as a potent chemoattractant for NP cells with similar responses observed to potent chemoattractants, such as fetal calf serum (FCS) . This result supports evidence that GDF6 can also act as a chemoattractant to chondrocytes . In a recent RNA sequencing study investigating regulatory networks controlling ECM synthesis in the human, IVD, GDF6, and GDF5 were identified as important human NP (but not AF) coregulatory gene networks .…”
Section: The Effect Of Supplementation With Gdfs On Disc Cells and Chmentioning
confidence: 52%
“…In a recent RNA sequencing study investigating regulatory networks controlling ECM synthesis in the human, IVD, GDF6, and GDF5 were identified as important human NP (but not AF) coregulatory gene networks . GDF6 supplementation also induces aggrecan expression and PG production in articular chondrocytes and human chondrocyte cell line C28/I2 …”
Section: The Effect Of Supplementation With Gdfs On Disc Cells and Chmentioning
confidence: 99%
“…Gene therapies or the addition of specific bone morphogenetic proteins were shown to accelerate the regeneration process, stimulate ECM production, or prevent the progression of annular injuries [ 90 , 91 , 92 , 93 , 94 ]. However, the delivery of genes into the AF cells has been technically challenging due to the low population of cells.…”
Section: Regenerative Strategiesmentioning
confidence: 99%
“…The effect of growth differentiation factors (GDFs) to enhance the anabolism-catabolism ratio in the ECM has been considered as an effective biomolecule-based regenerative strategy [ 93 , 97 ]. An increasing body of evidence indicated that GDFs were central to the IVD homeostatic processes, upregulation of the healthy cell marker genes in degenerative cells, and differentiation of mesenchymal stem cells to the NP cells [ 98 , 99 , 100 ].…”
Section: Regenerative Strategiesmentioning
confidence: 99%
See 1 more Smart Citation